Literature Review: Financial Literacy in The Context of Micro Enterprise Development and The Methods Used - Ferawati, Indah Wahyu; Fadah, Isti; Paramu, Hadi (Universitas Pendidikan Indonesia, 2024)
Financial literacy is an important factor in improving the performance of small firms. In today's highly competitive environment, small companies are trying to maintain their survival. One of the ways that companies maintain their survival is to improve performance by increasing understanding of financial literacy. This study aims to examine the determinants of financial literacy on the performance of small companies. This research uses the Systematic Literature Review (SLR) method. Articles were obtained from the Publish or Perish application with the keywords financial literacy and small business from Google Scholar and Scopus. The results showed that financial literacy has an important role in improving small business performance. It empowers business owners to make informed decisions, access resources effectively and drive sustainability, increase resilience and achieve growth in their enterprises.